Ethanol tolerant precious metal free cathode catalyst for alkaline direct ethanol fuel cells. (20th February 2017) - Grimmer, Ilena; Zorn, Paul; Weinberger, Stephan; Grimmer, Christoph; Pichler, Birgit; Cermenek, Bernd; Gebetsroither, Florian; Schenk, Alexander; Mautner, Franz-Andreas; Bitschnau, Brigitte; Hacker, Viktor
Graphical abstract: Highlights: Selective ORR catalysts are presented for alkaline direct ethanol fuel cells. Perovskite based cathode catalysts show high tolerance toward ethanol. A membrane-free alkaline direct ethanol fuel cell is presented. Abstract: La0.7 Sr0.3 (Fe0.2 Co0.8 )O3 and La0.7 Sr0.3 MnO3 −based cathode catalysts are synthesized by the sol-gel method. These perovskite cathode catalysts are tested in half cell configuration and compared to MnO2 as reference material in alkaline direct ethanol fuel cells (ADEFCs). The best performing cathode is tested in single cell setup using a standard carbon supported Pt0.4 Ru0.2 based anode. A backside Luggin capillary is used in order to register the anode potential during all measurements. Characteristic processes of the electrodes are investigated using electrochemical impedance spectroscopy. Physical characterizations of the perovskite based cathode catalysts are performed with a scanning electron microscope (SEM) and by X-ray diffraction showing phase pure materials. In half cell setup, La0.7 Sr0.3 MnO3 shows the highest tolerance toward ethanol with a performance of 614 mA cm −2 at 0.65 V vs. RHE in 6 M KOH and 1 M EtOH at RT. This catalyst outperforms the state-of-the-art precious metal-free MnO2 catalyst in presence of ethanol. In fuel cell setup, the peak power density is 27.6 mW cm −2 at a cell voltage of 0.345 V and a cathode potential of 0.873 V vs. RHE.